Differential combination of cytokine and interferon- γ +874 T/A polymorphisms determines disease severity in pulmonary tuberculosis. - Ambreen Ansari (Public Library of Science (PLoS), 2011)
Background Mycobacterium tuberculosis infects nearly 1/3 of the world population and this reservoir forms the largest pool from which new cases arise. Among the cytokines, IFN-γ is a key determinant in protection against tuberculosis. Single nucleotide polymorphisms (SNPs) in IFN-γ gene (+874 T/A) which determine TT high ((hi)), AA low ((lo)) and TA intermediate ((int)) responder phenotypes have shown variable associations with tuberculosis disease outcome in different ethnic populations. The objective of the current study was to analyze IFN-γ gene combinations with other IFN-γ regulating cytokine genes (IL-10, TNF -α, IL-6) to see the effect of gene- combinations on disease severity outcome in pulmonary tuberculosis. Methods and findings Study groups comprised of pulmonary TB patients stratified according to lung tissue involvement into mild (Pmd = 74) or advance (Pad = 23) lung disease and compared with healthy controls (TBNA = 166). Genotype analysis was carried out using amplification refractory mutation system-PCR (ARMS-PCR). IFN-γ gene (+874 T/A) functional SNP combinations in TNFα (-308 G/A), IL-10 (-1082 A/G) and IL-6 (-174 G/C) were analyzed. Single gene analysis (Pearson χ²) showed a dominant association of IFN-γ TT (hi) genotype (p = 0.001) and T allele (p = 0.001) with mild disease. IFN-γ(lo) -IL-10(lo) genotype combination was associated with advanced disease (p = 0.002). IFN-γ(hi) -IL-6(hi) combination was associated with mild disease (p = 0.0005) while IFN-γ(lo) -IL-6(int) was associated with protection against both forms of pulmonary disease (p = 0.002). Conclusion Our results show that a limited number of IFN-γ gene combinations with other cytokine functional SNPs determine the outcome of disease severity in tuberculosis.